Condiciones ambientales del internamiento penitenciario y las sentencias elevadas y su influencia en el desarrollo de trastornos del estado de ánimo, de las personas privadas de libertad del Centro de Privación de Libertad de personas adultas en conflicto con la ley de Loja y Zamora Chinchipe, 2017 - 2018 - Ordóñez Hurtado, Karen Gabriela (2018)
When a person is admitted to a detention center will undergo a traumatizing experience affect their state inevitably. The present investigation "Environmental conditions of the penitentiary internment and the high sentences, and their influence in the development of Mood Disorders in the people deprived of the Adults Deprivation of freedom Center of Loja", has as purpose to identify how the environmental conditions and high sentences influence the development of Mood Disorders in people deprived of the Adults Deprivation of freedom Center of Loja. The investigation was qualitative-quantitative, descriptive, of cross-sectional type. The same were applied to a sample of 60 inmates deprived of their liberty, in addition the technique applied to collect the information were a structured survey, a structured psychological clinical history and Millon Clinical Multiaxial Inventory III , which allowed processing the information, consolidating data and results to verify that the environmental conditions of the prison detention and the high sentences do influence the development of mood disorders in people deprived of freedom, concluding that they present a high index of mood disorders, among them we have mild depressive episode and masked depression. In addition, it was found that deprivation of liberty is a risk factor, which generates alterations in the person affectivity. Key words: Disorder, Depressive episode, penitentiary internment, environmental conditions, risk factor, adaptation.